2006
DOI: 10.1037/0735-7044.120.5.1084
|View full text |Cite
|
Sign up to set email alerts
|

Differential responsiveness to fluoxetine during puberty.

Abstract: In male golden hamsters (Mesocricetus auratus), attack frequency decreases during puberty. As serotonin inhibits offensive responses in adult hamsters, it is hypothesized that the serotonin system becomes upregulated in the hypothalamus during puberty. This hypothesis was tested through acute treatment with fluoxetine, a serotonin reuptake inhibitor, as well as through analysis of serotonin innervation in specific brain areas. In adults, fluoxetine treatment inhibited aggressive behavior. In juveniles, high do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…It was previously hypothesized that enhanced aggression in the presence of smaller and younger intruders was associated with altered expression of vasopressin and/or serotonin receptors [Delville et al, 1998]. Interestingly, more recent studies have shown that serotonin innervation of the anterior hypothalamus increases during puberty [Taravosh-Lahn et al, 2006], suggesting that the effects of social stress on the development of offensive responses could be mediated by an accelerated change in serotonin innervation of the anterior hypothalamus. Future studies will be required to explore this possibility.…”
Section: The Biobehavioral Effects Of Stress Are Age Dependentmentioning
confidence: 97%
“…It was previously hypothesized that enhanced aggression in the presence of smaller and younger intruders was associated with altered expression of vasopressin and/or serotonin receptors [Delville et al, 1998]. Interestingly, more recent studies have shown that serotonin innervation of the anterior hypothalamus increases during puberty [Taravosh-Lahn et al, 2006], suggesting that the effects of social stress on the development of offensive responses could be mediated by an accelerated change in serotonin innervation of the anterior hypothalamus. Future studies will be required to explore this possibility.…”
Section: The Biobehavioral Effects Of Stress Are Age Dependentmentioning
confidence: 97%
“…Moreover, because of their low affinity for neural receptors (i.e., muscarinic, histaminic, adrenergic, 5-HT1a, 5-HT1b), SSRIs are an ideal class of compounds for studying the selective and specific effects of increased 5-HT neurotransmission on aggressive behavior (van Harten 1993;Wong et al 1983). The effects of SSRIs on aggression have been examined in various animal models, behavioral paradigms, and species (Clotfelter et al 2007;Grimes and Melloni 2002;Lynn et al 2007;Sperry et al 2005;Taravosh-Lahn et al 2006). Nonetheless, the role of the serotonergic system on aggression is still inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…This cross linkage is in play during all four stages of aggressive interaction, modifying predisposition, motivation, and active aggression. This interface across circuitries is apparently developed during fetal through pubertal maturation, as stress-related transmitters such as 5-HT are less effective inhibiting aggression during puberty than in adults (Taravosh-Lahn et al, 2006). When stressful conditions are present during development, effects can be measured in the neural circuitries that regulate both aggression and stress, and in some brain regions those circuitries coincide.…”
Section: Cross Linkage Of Aggression and Stress Circuitrymentioning
confidence: 99%
“…Thus, if the brain serotonergic system is mediating the effects of elevated dietary Trp on aggressive behavior mechanisms other than increased 5-HT biosynthesis and release are likely to be involved. It is noticeable that the antidepressive effects of SSRI show a time course strikingly similar to the anti-aggressive effects of Trp; although the effects of SSRI on aggressive behavior can be as rapid as a single treatment (Perreault et al, 2003;Taravosh-Lahn et al, 2006). Also, similar to elevated dietary Trp, a 1-week treatment with citalopram reduces aggressive behavior in rainbow trout Even though the long-term stress-induced elevation in brain serotonergic activity (during stages 1 or 4) is likely to be an important factor mediating behavioral inhibition in subordinate animals, other neurotransmitter systems are most likely to also be involved.…”
Section: Serotonergic Inhibition Of Aggressionmentioning
confidence: 99%